Cellulose Biomaterials for Tissue Engineering - Hickey, Ryan J.; Pelling, Andrew E. (Frontiers in Bioengineering and Biotechnology, 2019)
A fundamental understanding of the nanoscale details of the environment is essential for designing biomaterials that mimic the natural cellular milieu. Many features of the local environment have profound influences on cell adhesion, proliferation, maturation, and differentiation. As such, small differences in nanostructure can have macroscale impacts on tissue function. In this review, we highlight the importance of nanostructure of cellulose-based biomaterials to allow cellular adhesion, the contribution of nanostructure to macroscale mechanical properties, and several key applications of these materials for fundamental scientific research and biomedical engineering. Cellulose is a diverse material with tunable properties and can be applied to systems with vastly different biochemical and biophysical environments. Cellulose-based biomaterials offer some important advantages over conventional synthetic materials and show great promise to advance the frontier of scientific knowledge. Here we provide an up-to-date summary of the status of the field of cellulose-based biomaterials in the context of bottom-up approaches for tissue engineering. We anticipate that cellulose-based material research will continue to expand because of the diversity and versatility of biochemical and biophysical characteristics highlighted in this review.